Taxing the Gender Gap: Labor Market Effects of a Payroll Tax Cut for Women in Italy - Enrico Rubolino (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper studies the labor market effects of a large employer-borne payroll tax cut for unemployed women, introduced in Italy since 2013. I combine social security data with several empirical approaches, leveraging the time-limited application of the tax scheme and discontinuities in eligibility criteria across municipalities, cohorts, and occupations. I find that the payroll tax cut generates long-lasting growth in female employment, reduces the time spent on welfare, and spurs business growth, without crowding out male employment. By contrast, the tax cut does not raise net wages, suggesting that tax incidence is mostly on firms. A cost-benefit analysis implies that the net cost of the policy is nearly half of the budgetary cost. These findings suggest that employer-borne payroll tax cuts are an efficient strategy to raise demand for female labor and tackle the gender employment gap, but they are not sufficient for reducing the gender pay gap.
Keywords: H22; J21; J31; 330; gender gap; female employment; payroll tax; tax incidence